👤

3. Find k so that x + 4 is a factor of x2 - kx + 8​

Sagot :

✏️FACTOR THEOREM

[tex]\red{••••••••••••••••••••••••••••••••••••••••••••••••••} [/tex]

[tex] \underline{\mathbb{PROBLEM}:} [/tex]

  • Find k so that x + 4 is a factor of x² - kx + 8

[tex]\red{••••••••••••••••••••••••••••••••••••••••••••••••••} [/tex]

[tex] \underline{\mathbb{ANSWER}:} [/tex]

[tex] \qquad\LARGE » \tt\: \green{k = \text-6} [/tex]

[tex]\red{••••••••••••••••••••••••••••••••••••••••••••••••••} [/tex]

[tex] \underline{\mathbb{SOLUTION}:} [/tex] In factor theorem, (x - r) is a factor of polynomial P(x) if and only if P(r) = 0. Let (x + 4) equal to zero then substitute it to the function.

  • [tex] \sf P(x) = x^2 - kx + 8 \:;\quad x = \text-4 [/tex]

  • [tex] \sf P(\text-4) = (\text-4)^2 - k(\text-4) + 8 [/tex]

  • [tex] \sf P(\text-4) = 16 + 4k + 8 [/tex]

  • [tex] \sf P(\text-4) = 24 + 4k [/tex]

» Since (x + 4) is a factor of P(x), then P(-4) is equal to zero.

  • [tex] \sf 0 = 24 + 4k [/tex]

  • [tex] \sf\text-4k = 24 [/tex]

  • [tex] \sf\frac{\cancel{\text-4}k}{\cancel{\text-4}} = \frac{24}{\text-4} \\ [/tex]

  • [tex] \sf k = \text-6 [/tex]

[tex] \therefore [/tex] The value of [tex] k [/tex] that will make (x + 4) a factor to the polynomial is -6.

[tex]\red{••••••••••••••••••••••••••••••••••••••••••••••••••} [/tex]

(ノ^_^)ノ